Hypothyroidism and hyperprolactinemia in women with primary and secondary infertility - Bari, Shamima; Begum, Rokeya; Akter, Qazi Shamima (IMC Journal of Medical Science, 2020)
Background and objectives: Infertility is a global health problem including Bangladesh. Altered thyroid and prolactin levels have been implicated as a cause of infertility. The study was undertaken to find out the serum thyroid hormones and prolactin status in women with primary and secondary infertility. Methods: Women with primary and secondary infertility were enrolled. Fertile age-matched women were included as control. The anthropometric details (age, height and weight) were recorded. Overnight fasting blood sample was collected on 2nd day of menstrual cycle of the follicular phase. Serum thyroid stimulating hormone (TSH), free tri-iodothyronine (FT3) and free thyroxine (FT4) were measured by enzyme-linked immunosorbent assay (ELISA). Serum prolactin (PRL) was estimated by radioimmunoassay. Results: A total of 150 women were enrolled in the study. Out of 150 women, 50 had primary and 50 had secondary infertility while 50 women were age-matched fertile women as control. The mean TSH levels of both infertility groups were significantly higher than that of fertile women. Regarding thyroid function, 24% and 28% of women with primary and secondary infertility had hypothyroidism respectively. The serum prolactin level was high in 42.9% and 50% of hypothyroid cases in primary and secondary infertility groups respectively. Conclusion: The study has demonstrated high occurrence of hypothyroidism with raised serum prolactin levels among infertile females emphasizing the importance of estimating both serum TSH and prolactin in infertility. Ibrahim Med. Coll. J. 2020; 14(1): 41-46